The key drivers in transforming Universiti Teknologi MARA into a sustainable green campus / Arnis Asmat ... [et al.] - Asmat, Arnis; Khalid, Khairi; Ahmad, Khairun Najiah; Dass, Laura Christ; Mohamad Zamri, Sharil Fadli; Sulaiman, Muhammad Azwan; Buyong, Faeiza; Ahmad, Che Bon (2023)
The transformation of universities into sustainable green campuses has become a critical imperative in addressing environmental challenges and promoting sustainable practices. This abstract explores the key drivers that motivate UITM to embark on this transformational journey. It highlights the role of students, faculty, and staff as change agents, the importance of institutional leadership and commitment, the influence of sustainability policies and regulations, the significance of financial considerations, and the impact of community engagement and partnerships. By understanding these key drivers, universities can effectively navigate the path toward becoming sustainable green campuses, fostering a culture of environmental responsibility and creating a positive impact on both campus life and the broader community. The objective of this paper is to highlight the key drivers in transforming Universiti Teknologi MARA into a sustainable green campus. Method involves compiling practices of green initiatives implemented on campus. Findings highlight implementation of sustainable practices is essential for successfully transforming a university into a sustainable green campus, which involves incorporating energy saving practices, promoting water conservation measures, encouraging waste reduction and recycling, prioritising green building designs, and engaging the campus community in environmental education and sustainable practices.